Multi-omics analyses the effect of Bifidobacterium longum subsp. longum BL21 supplementation on overweight and obese subjects: a randomized, double-blind, placebo-controlled study. - Wang, Xiaoya; Xing, Zefeng; Wang, Rui; Zhang, Guoming; Liu, Guodong; Li, Zhen; Li, Lixiang (Nutrition & Metabolism, 2025)
Background: Bifidobacterium longum subsp. longum BL21 has demonstrated promise in alleviating gut microbiota disturbances and metabolic regulation in high-fat diet-induced obesity and type 2 diabetes mellitus models. However, the effect of probiotic B. longum BL21 on overweight and obese individuals remain unclear. Methods: A randomized, double-blind, placebo-controlled trial was performed, and 66 adult individuals were assigned to receive either BL 21 (2*1010 colony-forming units per day along with 3 g of maltodextrin) or placebo (3 g of maltodextrin daily) for 8 weeks. Multi-omics analyses were employed to evaluate the impact of the B. longum strain BL21 on gut microbiota, serum metabolomics, body weight and lipids profiles in overweight and obese participants. Results: Following the intervention, both the BL21 group (1.22 ± 2.78, P = 0.02) and placebo group (0.98 ± 2.06, P = 0.01) demonstrated significant body weight reductions, with no statistically significant intergroup difference observed (P = 0.81). Notably, only the BL21 group exhibited a significant reduction in triglyceride levels compared to baseline (0.21 ± 1.09, P = 0.04). Microbiota analysis indicated that BL21 intervention significantly changed the β-diversity at week 8 compared with placebo group. The genera of Parasutterella, Parabacteroides, Blautia, Dorea, Butyricicoccus enriched in BL21 group. Metabolomics results indicated that sphingolipid metabolism, biotin metabolism and protein digestion and absorption were the top altered pathway in BL21 group compared with placebo group after intervention. Conclusion: B. longum subsp. longum BL21 may be a beneficial candidate to modulate the gut microbiota and triglyceride metabolism of overweight and obese individuals. Trial registration: Clinical trial registration number: NCT06140641. Date of registration: November 17, 2023.